2016
DOI: 10.1111/nmo.12910
|View full text |Cite
|
Sign up to set email alerts
|

Cough reflex attenuation and swallowing dysfunction in sub‐acute post‐stroke patients: prevalence, risk factors, and clinical outcome

Abstract: Prevalence of subacute post-stroke OD and swallow safety impairments was much higher than CRT attenuation, and risk factors strongly differed suggesting that the swallow response receives a stronger cortical control than the cough reflex. OD has a greater impact on PSP clinical outcome than impaired cough, the poorest prognosis being for patients with both airway protective dysfunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Similarly, Vilardell et al . found no association between stroke laterality and impaired efficacy of the cough response to inhalation of citric acid .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, Vilardell et al . found no association between stroke laterality and impaired efficacy of the cough response to inhalation of citric acid .…”
Section: Discussionmentioning
confidence: 84%
“…Impaired cough reflex was not related to lesions in one specific hemisphere in our study. Similarly, Vilardell et al found no association between stroke laterality and impaired efficacy of the cough response to inhalation of citric acid [16].…”
Section: Lesion Lateralizationmentioning
confidence: 95%
“…Preserved swallowing and cough functions are thus essential in preventing deep aspirations and consequent chest infections. If both responses fail, silent aspiration (an aspiration without cough) will occur, a dangerous event because of the difficulties in detecting it clinically and its severe consequences [26].…”
mentioning
confidence: 99%
“…Past studies have shown that the majority of patients with left MCA [13] show weak or absent VC and suggested laterality in VC with the left cerebral hemisphere playing a dominant role in the voluntary control of cough. However, other studies failed to associate RC with a specific hemisphere [8,38].…”
Section: Discussionmentioning
confidence: 94%